2020
DOI: 10.3389/feart.2020.00322
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Afro-Asian Monsoon Fringe Since Last Glacial Maximum

Abstract: Geological records indicated the termination of the Holocene Thermal Maximum (dramatic drying) occurred progressively later at lower latitudes in both North Africa and East Asia, along with the coherent weakening of local summer monsoon. Here we show that this time-transgressive evolution was dominated by the southward migration of monsoon fringe (shrinking monsoon domain) under monsoon weakening, as illustrated in a transient climate-terrestrial ecosystem model simulation. The monsoon fringe retreating southw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Shi and Yan (2019) found that the evolution of precipitation associated with the EASM, South ASM, and North African summer monsoon exhibited the characteristic of hemispheric synchrony since the LGM, and that Asian-African summer monsoonal precipitation generally increased between the LGM and 10 Kyr BP and then decreased subsequently. It is generally considered that such orbital-scale climatic changes over monsoonal Asia were predominantly caused by orbital-induced variation in insolation (Cheng et al, 2020;Lu et al, 2019). In addition, proxy records and TraCE-21ka simulations both revealed a Holocene wetting tendency in ACA (F. Chen et al, 2008Chen et al, , 2016.…”
mentioning
confidence: 99%
“…Shi and Yan (2019) found that the evolution of precipitation associated with the EASM, South ASM, and North African summer monsoon exhibited the characteristic of hemispheric synchrony since the LGM, and that Asian-African summer monsoonal precipitation generally increased between the LGM and 10 Kyr BP and then decreased subsequently. It is generally considered that such orbital-scale climatic changes over monsoonal Asia were predominantly caused by orbital-induced variation in insolation (Cheng et al, 2020;Lu et al, 2019). In addition, proxy records and TraCE-21ka simulations both revealed a Holocene wetting tendency in ACA (F. Chen et al, 2008Chen et al, , 2016.…”
mentioning
confidence: 99%